The Impact of Information Technology Flexibility on the Competitive Performance of Ports through the Mediating Role of Supply Chain Capabilities (An analytical study on a sample of individuals working in Umm Qasr port) - Al Taweel , Zaidoon (The Gulf Economist, 2023)
The information technology of flexibility (ITF) and its relationship to competitive performance is one of the important topics that are still in the exploratory stages, especially in Arab environments, and this study was based on dynamic capabilities. This study was applied in the General Company for Ports of Iraq / um Qasr Port in Basra. The current study relied on the descriptive analytical approach and the study data was collected using the questionnaire tool that was distributed to the study sample of 368 working individuals. Through the use of statistical methods in my program (SPSS. V.24 _ AMOS. V.24) The study reached several conclusions and recommendations. The most important of which is the positive and direct impact of(ITF) on competitive performance and indirectly through supply chain capabilities. The study recommends the need to pay attention to the capabilities of the supply chain in terms of speed of response and coordination, integration of activity and the availability of the ability to transfer and exchange information, as the role of information technology flexibility and its positive impact is clearly visible, and its impact extends through the capabilities of the supply chain, which is reflected in improving the overall performance of ports.